2004
DOI: 10.1007/bf02385580
|View full text |Cite
|
Sign up to set email alerts
|

Analyticity of the density of electronic wavefunctions

Abstract: We prove that the electronic densities of atomic and molecular eigenfunctions are real analytic in R 3 away from the nuclei.Date: November 22, 2002.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(79 citation statements)
references
References 12 publications
1
78
0
Order By: Relevance
“…and its total current by j t := j + ρA + curl m, where the magnetization of a state is defined in (15). The Hamiltonian that we consider is the many-body Pauli operator…”
Section: 2mentioning
confidence: 99%
“…and its total current by j t := j + ρA + curl m, where the magnetization of a state is defined in (15). The Hamiltonian that we consider is the many-body Pauli operator…”
Section: 2mentioning
confidence: 99%
“…We also assume throughout this paper that the potential V equals to −Z/|r| in the neighborhood of 0, and belongs to C ∞ loc (R 3 \ R) ∩ L 2 # (Ω). It was shown in [23,24,25] that the exact electron densities are analytic away from the nuclei and satisfy certain cusp conditions at the nuclei. The plane wave approximations can not have as good convergence rate as (2.1) due to the cusps at the nuclear positions.…”
Section: Preliminarymentioning
confidence: 99%
“…For eigenvalue problems with singular potentials in full-potential calculations, plane waves are inefficient bases for describing the cusps at the nuclei positions [23,24,25,28]. In contrast, it is observed that a significant part of the rapid oscillations can be captured by atomic orbitals such as Gaussians and Slater-type orbitals [27,34], which have been widely used in quantum chemistry (we refer to [7,18] for their numerical analysis).…”
Section: Introductionmentioning
confidence: 99%
“…For N = 1, we take ρ = |ψ| 2 . The regularity result is the following FHHS2]. The density ρ is real analytic on R 3 \ {R 1 , · · · , R L }.…”
mentioning
confidence: 98%
“…In [FHHS1], it is proved that ρ is smooth on R 3 \{R 1 , · · · , R L }. This result is then used in [FHHS2] to derive the analyticity.…”
mentioning
confidence: 99%